Empirical study on transformational leadership, deviant behaviour, job performance, and gender : evidence from a study in Bangladesh - Uddin, Mohammad Aftab (2017)
This paper studies the relationships between transformational leadership, deviant behaviour, job performance, and gender. Data collected from 160 respondents from different organisations using the convenience sampling method was analysed using descriptive statistics, bivariate correlation, and regression analysis. Results reveal that there is a negative relationship between transformational leadership and deviant behaviour, while a positive association exists between transformational leadership and job performance, with a negative correlation between deviant workplace behaviour and job performance. Gender analysis shows that female ratings for different indicators, such as transformational leadership, deviant behaviour, and job performance were not significantly distinct from those of males. The main implication of this research is that it informs executives how transformational leadership and deviant behaviour affect job performance. Limitations and future research directions are discussed.